Double diffusive time-dependent MHD Prandtl nanofluid flow due to linear stretching sheet with convective boundary conditions. (2nd January 2023) - Patil, Amar B.; Patil, Vishwambhar S.; Humane, Pooja P.; Shamshuddin, MD.; Jadhav, Mehul A.
ABSTRACT: The focus of this study is to examine cross-diffusion effects on radiative and reactive Prandtl nanofluid due to a convectively heated stretching surface. The present flow problem is considered under the assumption that the external magnetic field is applied to study the nanofluid behavior and thermal radiation considered, for a complete understanding of magnetohydrodynamics of the flow. The governing system of the nonlinear partial differential equations of the flow problem is remodeled with suitable similarity invariants and obtained the system of nonlinear ordinary differential equations. The transformed ODEs with their modified boundary conditions deal with the employment of the Runge-Kutta technique using computation shooting schema with MATLAB software. The consequence of numerous leading parameters on the fluid velocity, temperature, concentration, and engineering quantities profiles are discoursed and presented through graphical illustration. Moreover, the current work is also equated with the available work for limiting cases. It is found that the external magnetic field diminishes the motion of fluid and improvement in heat transfer. Concentration performance improvises on cross diffusion, thermophoresis, and Brownian motion impacts.